FACTORS INFLUENCING THE ACCEPTANCE OF BLENDED LEARNING BY EARLY CHILDHOOD UNDERGRADUATE STUDENTS - HUANG, JUELIANG; PHONGSATHA, THANAWAN (Scholar: Human Sciences, 2022)
The mixed-method research approach was applied to explore early childhood major students' levels of acceptance and attitudes towards blended learning based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) and College and University Classroom Environment Inventory (CUCEI). Three hundred sixty-three undergraduate early childhood major students in China participated in the study. The Structural Equation Modeling (SEM) analysis was used to determine which variables in the UTAUT2 and CUCEI significantly impacted blended learning acceptance. The interview data supplemented the findings of the quantitative data. It was found that social influence and classroom environment significantly impacted blended learning acceptance. Results also indicated that blended learning is more likely to be accepted and used because of the ease of its use and the convenience it offers, as well as promoting a better social and classroom environment. However, the blended learning acceptance was not correlated with performance expectancy, effort expectancy, hedonic motivation, facilitating condition, and price value. Based on these findings, the researcher provided suggestions for decision-makers regarding using and accepting blended learning in their institutions. Administrators and educators can use this study's findings to guide their implementation and improvement of blended learning.